Constraints on the waging of war : an introduction to international humanitarian law - Kalshoven, Frits; Zegveld, Liesbeth ([S.l.] : Cambridge University Press, 2011)
This fully revised fourth edition of Constraints on the Waging of War considers the development of the principal rules of international humanitarian law from their origins to the present day. Of particular focus are the rules governing weapons and the legal instruments through which respect for the law can be enforced. Combining theory and actual practice, this book appeals to specialists as well as to students turning to the subject for the first time.
Keywords: Combatants and noncombatants (International law); Geneva Conventions (1949); Humanitarian law; International relations; War (International law); War victims--Legal status, laws, etc; Weapons--Law and legislation